KEANEKARAGAMAN BURUNG DI BERBAGAI TIPE HABITAT PADA EKOSISTEM RAWA GAMBUT YANG TERDEGRADASI DESA TANJUNG LEBAN AREA TRANSISI CAGAR BIOSFER GIAM SIAK KECIL BUKIT BATU, RIAU - Abdi Nazirwan; Haris Gunawan; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
High degradation of peat land in the village of Tanjung Leban, Bengkalis was suspected to affect the bird  fauna in this  region. This study aimed  to determine species diversity and  abundance of birds in the village of Tanjung Leban on three types of habitat : burned land,  rubber, and oil palm plantations.  The study was conducted from March to May 2014.The combination of transects with point count and mist nets were used in this study. The diversity of bird in study area was analyzed usingShannon index diversity. A total of 39 bird species were observed, they were grouped into 26 families.  Columbidae and Pycnonotidae  were the  families  that havethe  highest  abundance compared with other families.  Shannon indexesfor the  diversityof  the birdwhich    observed in  threehabitats ranged  from 2.275 to 2.699. The  highest value of  Shannon index  was found in the rubber plantation habitat.